Evaluating the Antioxidant Activity and Stability of Pigmented Rice Extract - Tagor M Siregar; Daniel C Miarsa (The University of Lampung, 2024)
This study aims to evaluate the antioxidant activity and stability of the extract of pigmented rice. Pigmented rice powder from 6 different varieties including Subang, Jowo Melik, Andel Abang, Bukittinggi, Cempo Merah, and Cempo Ireng) was macerated using ethanol with concentrations of 96% and 70%. Next, the rice extract was tested for stability to pH (1, 3, 5, 7, 9) and temperature (20°, 40°, 60°, 80°C). Results revealed that extract of Subang black glutinous rice using 96% ethanol resulted the highest antioxidant activity of 11.11±2.04 mg FeSO4/g, with an overall anthocyanin, flavonoids, phenolic contents of respectively 28.22±1.14 mg CE/g, 2.91±1.13 mg QE/g, and 3.46±1.59 mg GAE/g. The physiochemical properties of the rice extract were affected by the difference of pH. The increase in pH resulted in a decrease in antioxidant activity, total anthocyanin, and the values of color attributes (L*, a*, b*, C*, and ºHue) of the rice extracts. Temperature did not affect the physiochemical properties of the extract. The antioxidant activity, total anthocyanin, and color attributes of the rice extract were typically stable when the temperature rose from 20°C to 80°C. The extract at pH 1 and 80ºC treatment exhibited slightly higher yield based on antioxidant activity, total anthocyanin content, a* value, and ºHue with the values of 16.92±1.73 mg FeSO4/g, 33.90±2.33 mg CE/g, 21.55±0.54, and 30.04±0.57, respectively. Keywords: Anthocyanin, antioxidant activity, pH, pigmented rice, temperature.